NEXUS ANTARA PEMBANGUNAN BERKELANJUTAN DAN REDUKSI KEMISKINAN WILAYAH PESISIR DI JAWA TIMUR - Shodiqi, Fahrur Rozi; Prianto, Fajar Wahyu; Diartho, Herman Cahyo (Growth, 2024)
Coastal areas are often seen as marginalized areas, tending to be the focus of poverty. In East Java, coastal areas experience poverty rates 9-10% higher than the average for other regions. This research aims to analyze factors such as economic growth, labor force participation, human development, and access to clean water that influence poverty in the coastal region of East Java, as well as designing poverty reduction scenarios using a dynamic systems approach. The analysis method uses explanatory research with a quantitative approach, including regression analysis using Ordinary Least Squares (OLS) and System Dynamics. Panel data from 22 districts/cities in the coastal region of East Java from 2013 to 2022 were used in this research. The results of the Fixed Effect Model (FEM) test show that GDP per capita has a negative and significant impact on poverty in the coastal region of East Java. The labor force participation rate and regional spending have a positive but not significant influence. The Human Development Index influences poverty negatively and significantly, while access to clean water influences it positively and significantly. Dynamic system simulations show that by involving several variables simultaneously with the assumption that each increase in GRDP per capita is 4% and TPAK, HDI, and AAB is 1 percent, there will be a decrease in the number of poor people in the coastal areas of East Java Province by 1 percent.